SITUATION AND SOLUTIONS TO IMPROVE THE QUALITY OF TEACHING FRENCH FOR BUSINESS AT FOREIGN TRADE UNIVERSITY - Giang, Do Thi Thu (VNU Journal of Foreign Studies; Vol 36 No 2DO - 10.25073/2525-2445/vnufs.4543, 2020)
The modules of language for buniness play an important role in the program for students majoring in French for Business - French Language at Foreign Trade University. In order to improve the quality of student output, it is essential to improve the quality of these modules. Therefore, we have conducted a descriptive study, based on basic research tools such as observations, surveys, interviews with students, lecturers and employers to evaluate the current status of teaching at our university. The results include: (1) Identifying outstanding issues in each of the constituent elements of teaching French for business, namely the content and training program, teachers, learners, and learning materials. (2) Proposing solutions in order to improve the quality of teaching.